2019
DOI: 10.1080/00102202.2019.1594797
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Activated Carbon Monolith Co3O4-Based Catalyst for Simultaneous SO2/NOx Removal from Flue Gas Using Response Surface Methodology

Abstract: Coal combustion is a primary source of acid gases such as sulfur dioxide (SO2) and nitrogen dioxide (NOx); meanwhile, their effects are detrimental to man and the environment. In this work, three different adsorbents were developed by loading Co3O4 on monolith using pore volume impregnation, deposition precipitation, and hydrothermal methods (HMs) of synthesis.The breakthrough study in the simultaneous SO2 and NOx removal from flue gas revealed that the performance of the adsorbent developed by HM was better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The Freundlich isotherm confirms CDs as having defined surface heterogeneity and the exponential distribution of active sites [70]. The adsorption process as explored by both Langmuir The values of the Langmuir constant K L and the monolayer capacity q max can be evaluated from the three forms of Langmuir adsorption models.…”
Section: Adsorption Equilibriummentioning
confidence: 84%
See 1 more Smart Citation
“…The Freundlich isotherm confirms CDs as having defined surface heterogeneity and the exponential distribution of active sites [70]. The adsorption process as explored by both Langmuir The values of the Langmuir constant K L and the monolayer capacity q max can be evaluated from the three forms of Langmuir adsorption models.…”
Section: Adsorption Equilibriummentioning
confidence: 84%
“…Since the processes followed the pseudo second-order equation, it literally suggests that the adsorption is mainly by simple chemisorption reaction occurring between the lead ions and the surface functional groups of CDs [49,50]. The Freundlich isotherm confirms CDs as having defined surface heterogeneity and the exponential distribution of active sites [70]. The adsorption process as explored by both Langmuir and Freundlich isotherms have proven favorability of the adsorption process.…”
Section: Pseudo First and Second-order Kinetic Modelsmentioning
confidence: 99%
“…The peaks at 1072 and 1383, cm -1 assigned to Si-O stretching vibrations indicates the presence of quartz and cerrusite, the absorption at at 1320-1210 cm −1 is stretching vibration (C-O) of phenol and ether (Bora et al, 2021;Rawat and Yadav, 2020;Silas et al, 2019), the stretching band of aromatic compounds can be observed at 1615 cm -1 peak (Boral et al, 2021), 2800-3000 cm -1 is due to the stretching vibration aliphatic and alicyclic (-CH 3 , -CH 2 and -CH) groups carbon where different aliphatic -CH bonds is associated to sub-bituminous coal (Manoj and Elcey, 2013;Rodrigues et al, 2020). According to (Nyakuma et al, 2021), sub-bituminous coals have the potential to be liquefied and used to make synthetic crude oil and tar.…”
Section: Results Of Ftir Spectramentioning
confidence: 99%
“…AC has been investigated for SO x and NO x [99,100], H 2 S [101], and CO 2 [100] sequestration at different process conditions. To optimize capture and selectivity of AC for specific gases, modification of the structure to increase its affinity for specific gases have been reported [102][103][104][105][106][107][108].…”
Section: Activated Carbon (Ac)mentioning
confidence: 99%